Cognitive and subjective effects of mephedrone and factors influencing use of a 'new legal high' - Freeman, Tom P.; Morgan, Celia J. A.; Vaughn-Jones, James; Hussain, Nahida; Karimi, Kash; Curran, H. Valerie (Addiction (Abingdon, England), 2012)
ABSTRACT Aims  Use of the stimulant drug mephedrone increased dramatically in 2009, and it is still available in the United Kingdom after being controlled in April 2010. This study aimed to assess mephedrone's acute cognitive and subjective effects. Design  A mixed within‐ and between‐subjects design compared 20 mephedrone users, first while intoxicated (T1) and secondly drug free (T2); and 20 controls twice when drug free (T1 and T2). Settings  Participants' own homes. Participants  Healthy adults recruited from the community. Measurements  Subjective effects, episodic and working memory, phonological and semantic fluency, psychomotor speed and executive control at were assessed at T1 and T2. Trait schizotypy, depression, changes in mephedrone use since the ban and attitudes influencing use of a hypothetical new legal high were indexed at T2 only. Findings  Compared with controls, mephedrone users had generally impaired prose recall (P = 0.037) and higher scores in schizotypy (P < 0.001) and depression (P = 0.01). Mephedrone acutely primed a marked ‘wanting’ for the drug (P < 0.001), induced stimulant‐like effects, impaired working memory (P < 0.001) and enhanced psychomotor speed (P = 0.024). Impulsivity in mephedrone users correlated with the number of hours in an average (nearly 8 hour) mephedrone session (r = 0.6). Users would be drawn to use a new legal high if it were pure, had no long/short term harms, and was positively rated by friends or on the internet. Conclusions  Mephedrone impairs working memory acutely, induces stimulant‐like effects in users and is associated with binge use. Factors that influence users' attitudes to new drugs might help to predict future trends in use of the many new psychoactive substances emerging on the internet.